Meta-Analisis Efektivitas Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis dan Sikap Ilmiah - syafiatuz zahro (IAIN Kendari, 2020)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) model on students' critical thinking skills and scientific attitudes based on education level, learning materials and teaching materials used. This research used meta-analysis method. This research was obtained from 7 national scientific journals. Based on the results obtained based on the level of education, the PBL model is effectively used at the junior high school and senior high school levels. Based on learning materials, PBL models are used to develop critical thinking skills and scientific attitudes. Based on the learning material, the PBL model is more effective in using the human respiratory system material for critical thinking skills and scientific attitudes. Then based on the teaching materials, all teaching materials are effective when using the PBL model for critical thinking skill and scientific attitudes. Penelitain ini bertujuan untuk mengetahui efektivitas dari penerapan model Problem Based Learning (PBL) terhadap kemampuan berpikir kritis dan sikap ilmiah siswa berdasarkan jenjang pendidikan, materi pembelajaran dan bahan ajar yang digunakan. Metode yang digunakan adalah meta-analisis. Penelitian ini diperoleh dari 7 jurnal ilmiah nasional. Berdasarkan hasil yang diperoleh berdasarkan jenjang pendidikan, model PBL efektif digunakan pada jenjang SMA maupun SMP. Berdasarkan materi pembelajaran, model PBL untuk mengembangkan kemampuan berfikir kritis dan sikap ilmiah. Berdasarkan materi pembelajaran, model PBL lebih efektif menggunakan materi sistem pernapasan manusia untuk kemampuan berpikir kritis dan sikap ilmiah. Kemudian berdasarkan bahan ajar seluruh bahan ajar efektif jika menggunakan model PBL untuk berfikir kritis maupun sikap ilmiah.